High serum miR-223-3p expression level predicts complete response and prolonged overall survival in multiple myeloma patients undergoing autologous hematopoietic stem cell transplantation - Mikulski, Damian; Nowicki, Mateusz; Dróźdż, Izabela; Misiewicz, Małgorzata; Kościelny, Kacper Piotr; Okoński, Karol; Krawiec, Kinga; Perdas, Ewelina; Wierzbowska, Agnieszka; Fendler, Wojciech (Frontiers in Oncology, 2023)
Introduction: AHSCT is the treatment of choice for newly diagnosed patients with transplanteligible multiple myeloma (MM). However, considerable variability in response to autologous hematopoietic stem cell transplantation (AHSCT) results in only 50% of patients achieving complete response (CR) after AHSCT, which is directly associated with improved progression-free and overall survival (OS). In this study, we aimed to investigate the potential predictive role of selected serum miRNAs in MM patients who underwent AHSCT.Patients and methods: Serum expression level of 6 miRNAs: miR-221-3p, miR-15b-5p, miR-223-3p, miR-320c, miR-361-3p, and miR-150-5p was evaluated in 51 patients who underwent AHSCT. Blood samples were collected at two time points: before conditioning chemotherapy (T1) and fourteen days after transplant (+14) (T2).Results: All selected miRNAs significantly changed their expression level across the proceduretwo were up-regulated after AHSCT: hsa-miR-320c (FC 1.42, p<0.0001) and hsa-miR-361-3p (FC 1.35, p=0.0168); four were down-regulated: hsa-miR-15b-5p (FC 0.53, p<0.0001), hsa-miR-221-3p (FC 0.78, p=0.0004), hsa-miR-223-3p (FC 0.74, p=0.0015) and hsa-miR-150-5p (FC 0.75, p=0.0080). Notably, before AHSCT, hsa-miR-223-3p was down-regulated in International Staging System (ISS) III patients (FC=0.76, p=0.0155), and hsa-miR-320c was up-regulated (FC=1.27, p=0.0470). These differences became non-significant after AHSCT. Eight (15.69%) patients achieved CR before AHSCT and 17 patients (33.33%) at +100 days after AHSCT. In multivariate logistic regression analysis, achievement of CR after induction and hsa-miR-223-3p at T1 were independent predictors of CR after AHSCT. In multivariate Cox regression analysis, hsa-miR-223-3p at T1 expression level was associated with prolonged OS (HR 0.06, 95%CI: 0.00 -0.99, p=0.0488).Conclusions: Serum expression of hsa-miR-223-3p is a predictor of CR and prolonged OS in MM patients undergoing AHSCT.